N-acetylcysteine protect inner hair cells from cisplatin by alleviated celluar oxidative stress and apoptosis. (June 2022) - Wang, Weilong; Chen, Erfang; Ding, Xuerui; Lu, Peiheng; Chen, Jiawei; Ma, Pengwei; Lu, Lianjun
Abstract: Cisplatin is a well-known platinum-based chemotherapy drug widely used to treat a variety of malignant tumors. However, cisplatin has serious side-effects include nephrotoxicity and ototoxicity, Cisplatin chemotherapy causes permanent hearing loss at least 40% of treated patients. Our results showed that 20 mM N -acetylcysteine (NAC) can completely protect 50 μM cisplatin-induced hair cell loss in rat cochlear culture and protects against cisplatin-induced hair cell loss in zebrafish in vivo. The fluorescence intensity of mitochondrial ROS significantly increased after the cultures were treated with 15 μM cisplatin for 48 h and was decreased in the group treated with 15 μM cisplatin add 20 mM NAC. In addition, the number of TUNEL positive hair cells was increased after the cultures were treated with 15 μM cisplatin for 48 h and there are null in cisplatin and NAC co-treated group. Highlights: 20 mM N -acetylcysteine can protect completely 50 μM cisplatin-induced hair cell loss in rat cochlear culture NAC protects against cisplatin-induced hair cell loss in zebrafish in vivo Mitochondrial ROS significantly increased after the cultures were treated with cisplatin and was decreased in the group treated with cisplatin add NAC. The number of TUNEL positive hair cells was increased in cisplatin cultures and there are null in cisplatin and NAC co-treated group.